Electronic procurement implementation in Malaysia: suppliers' readiness - Kaliannan, Maniam; Hashim, Rugayah; Chandran, Suseela Devi (2011)
Quality, standard, productivity and service have become key words in the lexicon of public sector reform in many developed and some developing countries in recent years. Increasing prominence given to these terms with rising expectations and changing perceptions of customers, who constantly grave for delivery of high quality services. This in turn, exert constant pressure on public service personnel at all levels in pursuit of new ideas and innovation, especially in the context of three Es- economy, efficiency and effectiveness (Khan, 2002). Thus, there is a strong call for governments all over the world to improve the quality of their service delivery. In this regards, governments have adopted various means and methods to be more innovative and effective in order to fulfil the demands from the citizens. All the programs implemented aimed at transforming the ability and attitude of the public officials to be more proactive and participative in their jobs and duties. Major innovations started to take place in the public sector since the introduction of New Public Management (NPM) agenda in 1994 in the US (Khan, 2002). One of the leading innovations is the implementation of Information and Communications Technology (ICT) with an objective to reinvent the way government doing its business. A classic example often cited on lire-inventing government" strategy achievement was during Clinton/ AI Gore administration, when the civil service directed to make United States (US) work better and cost less. The achievement, as outlined below, was declared in a press release during the First Global Forum on Reinventing Government in 14th January 1999, organized by Division for Public Administration and Development Management under the auspicious of United Nation.